A comparison of heart rate training load and perceptual effort between masters and young cyclists - Borges, N. R.; Scanlan, A. T.; Reaburn, P. R.; Doering, T. M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Due to age-related changes in the psychobiological state of masters athletes, this brief report aimed to compare training load responses using heart rate (HR) and ratings of perceived exertion (RPE) during standardized training sessions between masters and young cyclists. Methods: Masters (n=10; 55.6 [5.0] y) and young (n=8; 25.9 [3.0] y) cyclists performed separate endurance and high-intensity interval training sessions. Endurance intensity was set at 95% of ventilatory threshold 2 for 1 hour. High-intensity interval training consisted of 6×30-second intervals at 175% peak power output with 4.5-minute rest between intervals. HR was monitored continuously and RPE collected at standardized time periods during each session. Banister training impulse and summated-HR-zones training loads were also calculated. Results: Despite a significantly lower mean HR in masters cyclists during endurance (P=.04; d=1.06 [±0.8], moderate) and high-intensity interval training (P=.01; d=1.34 [±0.8], large), no significant differences were noted (P>.05) when responses were determined relative to maximum HR or converted to training impulse and summated-HR-zone loads. Furthermore, no interaction or between-group differences were evident for RPE across either session (P>.05). Conclusions: HR and RPE values were comparable between masters and young cyclists when relative HR responses and HR training load models are used. This finding suggests HR and RPE methods used to monitor or prescribe training load can be used interchangeably between masters and young athletes irrespective of chronological age.